2009
DOI: 10.1007/s11267-009-9230-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Performance of a Permeable Reactive Barrier in Acid Sulphate Soil Terrain

Abstract: Deep drainage technique utilised for flood mitigation in low-land coastal areas of Australia during the late 1960s has resulted in the generation of sulphuric acid in soil by the oxidation of pyritic materials.Further degradation of the sub-surface environment with widespread contamination of the underlying soil and groundwater presents a major and challenging environmental issue in acid sulphate soil removal efficiency (> 95%) over this study period indicates that recycled concrete could successfully treat ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The experimental data contributes to knowledge, providing insight to PRB rejuvenation and enhancement of longevity using alkaline wastewaters and the study gains a valuable insight into the suitability of waste alkaline rejuvenation for future PRB installations, and additionally what this means for future PRB design and PRB technology. (Regmi et al, 2009) and alkaline wastewater chemistry (courtesy of Manildra Group) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental data contributes to knowledge, providing insight to PRB rejuvenation and enhancement of longevity using alkaline wastewaters and the study gains a valuable insight into the suitability of waste alkaline rejuvenation for future PRB installations, and additionally what this means for future PRB design and PRB technology. (Regmi et al, 2009) and alkaline wastewater chemistry (courtesy of Manildra Group) …”
Section: Discussionmentioning
confidence: 99%
“…This was the same batch of recycled concrete used in the pilot-scale PRB. The major cations in the recycled concrete are predominantly calcium (Ca, 57.3%), Fe (21.4%), Al (9.85%), magnesium (Mg, 5.27%), silica (Si, 3.06%) and others (3.04%) (Regmi et al, 2009).…”
Section: Reactive Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are thirteen primary mineral dissolution-precipitation reactions as shown in [3]. To confirm the adoption of only these thirteen reaction equations in the geochemical algorithm, inverse geochemical modelling has been carried out by [22] which consider all the possible mineral phases in the upstream of the PRB and inside the PRB. The results from inverse geochemical modelling confirmed that these thirteen reactions are the dominant reactions in terms of acid neutralisation.…”
mentioning
confidence: 99%